1995
DOI: 10.1128/iai.63.7.2604-2611.1995
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of acapsular Cryptococcus neoformans occurs via mannose and beta-glucan receptors, resulting in cytokine production and increased phagocytosis of the encapsulated form

Abstract: Cryptococcus neoformans is a pathogenic yeast and a major cause of opportunistic infection in AIDS patients. It is commonly found in an acapsular form in the environment, and infection is likely to occur by inhalation. The lung provides a suitable environment for capsule synthesis, and once encapsulated, C. neoformans becomes resistant to phagocytosis. A stable acapsular mutant of the organism is readily ingested by murine macrophages in vitro, indicating entry via constitutively competent receptors. We demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 33 publications
(42 reference statements)
2
56
0
4
Order By: Relevance
“…It is thought that the cell wall of M. furfur is composed of mannan and L-glucan, although their structures were not examined in detail [18]. We found, however, that M. furfur contains (1C3)-and (1C6)-L-D-glucans in cell wall by using 13 C-NMR (unpublished data). Thus the cell wall L-glucan would participate in the expression of IL-8 mRNA from phagocytes and subsequent induction of in£ammatory responses.…”
Section: Discussionmentioning
confidence: 81%
“…It is thought that the cell wall of M. furfur is composed of mannan and L-glucan, although their structures were not examined in detail [18]. We found, however, that M. furfur contains (1C3)-and (1C6)-L-D-glucans in cell wall by using 13 C-NMR (unpublished data). Thus the cell wall L-glucan would participate in the expression of IL-8 mRNA from phagocytes and subsequent induction of in£ammatory responses.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, the C. neoformans strain used in the study of Collins & Bancroft [37], although not described in detail, appears to be less virulent, since the number of injected yeast cells was 10 times higher than that used in our study. Despite the higher dose, it did not result in a lethal infection [37,38], and induced the expression of TNF-mRNA in vitro by macrophages [38]. These results indicate that TNFis copiously produced in infected sites and plays an important protective role.…”
Section: Discussionmentioning
confidence: 85%
“…Parallels were made to the polysaccharide-rich capsule of Cryptococcus neoformans, shown to confer antiphagocytic properties and downregulation of proinflammatory cytokine (IL-1b and TNF-a) production by monocytes (Kozel et al, 1988;Vecchiarelli et al, 1995). Uptake of acapsular C. neoformans by murine macrophages and induction of IL-1b, TNF-a and GM-CSF was controlled by mannose and b-glucan receptors and it was concluded that the capsule masks carbohydrate residues in the yeasts cell walls (Cross & Bancroft, 1995) in a similar way as the lipid capsule of Malassezia is speculated to in this study. Unfortunately, very little research has been performed to determine the composition of Malassezia cell wall, but it is known to contain high proportions of carbohydrate (Hechemy & Vanderwyk, 1968;Thompson & Colvin, 1970).…”
Section: Discussionmentioning
confidence: 99%